PENERAPAN STRATEGI PEMBELAJARAN AKTIF FORMASI REGU TEMBAK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI IPA SMA NEGERI 4 PEKANBARU - Irya, Syahrina; Erna, Maria; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Has made the application of active learning strategy of Firing Line to improve student achievement on the topic of Reaction Rate in class XI IPA SMAN 4 Pekanbaru. The research is a type of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA3 as the experimental class and students of class XI IPA2 as the control class. Experimental class is a class that is applied to active learning strategy of Firing Line while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 2,53>1,67, means that the application of active learning strategy of Firing Line can improve student learning achievement on the topic of Reaction Rate in class XI SMAN 4 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,78. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,68.Keywords: Firing Line, Active Learning, Achievement, Reaction Rate.